2021
DOI: 10.31111/vegrus/2021.40.108
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of vegetation after clearcutting bilberry spruce forests (middle taiga subzone of the European North-East of Russia)

Abstract: The communities of middle taiga spruce forests (ass. Linnaeo borealis–Piceetum abietis dryopteridetosum var. typica) and secondary communities formed after winter clearcuttings are described (Fig. 1) and classified according Braun-Blanquet (1964) approach using 81 relevés. Ellenberg ecological values (Ellenberg et al., 1991) were used to assess lighting (L), soil moisture (F), acidity (R) and nitrogen (N). The ordination was carried out using the NMS method. Both primary forest and secondary communities are cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The synphytoindication method [55] was designed to forecast the dynamics of forest species and types based on the impact intensity of environmental factors. The method is based on a wide range of front edge mathematical methods for data analysis, thereby allowing quantitative assessment of habitat parameters, including climate factors, based on the ecological specifics of plant species.…”
Section: European Vegetation Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The synphytoindication method [55] was designed to forecast the dynamics of forest species and types based on the impact intensity of environmental factors. The method is based on a wide range of front edge mathematical methods for data analysis, thereby allowing quantitative assessment of habitat parameters, including climate factors, based on the ecological specifics of plant species.…”
Section: European Vegetation Classificationmentioning
confidence: 99%
“…The method is based on a wide range of front edge mathematical methods for data analysis, thereby allowing quantitative assessment of habitat parameters, including climate factors, based on the ecological specifics of plant species. For example, it was found that an increase in annual average temperatures of 1-3 • starts succession processes, including changes in species and forest types [55].…”
Section: European Vegetation Classificationmentioning
confidence: 99%